2008
DOI: 10.1021/nl073022t
|View full text |Cite
|
Sign up to set email alerts
|

p-Type ZnO Nanowire Arrays

Abstract: Well-aligned ZnO nanowire (NW) arrays with durable and reproducible p-type conductivity were synthesized on alpha-sapphire substrates by using N2O as a dopant source via vapor-liquid-solid growth. The nitrogen-doped ZnO NWs are single-crystalline and grown predominantly along the [110] direction, in contrast to the [001] direction of undoped ZnO NWs. Electrical transport measurements reveal that the nondoped ZnO NWs exhibit n-type conductivity, whereas the nitrogen-doped ZnO NWs show compensated highly resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
180
1
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(196 citation statements)
references
References 60 publications
8
180
1
2
Order By: Relevance
“…Basically, to make p-type ZnO nanowires, group-V or group-I element atoms are needed to react and then diffuse through the defects of ZnO to replace oxygen or zinc atoms in ZnO. There have been many efforts using both vapor phase [252,253] and solution phase growth approaches [254]. For example, p-type doping of ZnO nanowire arrays has been reported by post-treatment of as-grown n-type ZnO nanowires, such as using NH 3 plasma treatment [255], and thermal deposition and diffusion of As from GaAs wafers [256].…”
Section: P-type Dopingmentioning
confidence: 99%
“…Basically, to make p-type ZnO nanowires, group-V or group-I element atoms are needed to react and then diffuse through the defects of ZnO to replace oxygen or zinc atoms in ZnO. There have been many efforts using both vapor phase [252,253] and solution phase growth approaches [254]. For example, p-type doping of ZnO nanowire arrays has been reported by post-treatment of as-grown n-type ZnO nanowires, such as using NH 3 plasma treatment [255], and thermal deposition and diffusion of As from GaAs wafers [256].…”
Section: P-type Dopingmentioning
confidence: 99%
“…Near the surface of the NW, many edge dislocations are found to support the dopinginduced stress. The NW growth direction is not perpendicular to the primary planes in forming the deviation from the upright ABABA stacking, implying a switch of the primary growth plane [6]. This means it is not easy to dope Ag with ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…However, p-type conductivity was not stable and converted to n-type three months later. Similarly, Yuan et al [2008] reported the growth by chemical vapor deposition (CVD) of nitrogen doped ZnO wires which showed p-type FET characteristics. Lu et al [2009] reported the growth of p-type ZnO nanowires also with CVD using Zn 3 P 2 as dopant.…”
Section: Introductionmentioning
confidence: 99%